Pengambilan Keputusan dan Preferensi Petani Menggunakan Pupuk Subsidi di Kecamatan Sentra Padi Kabupaten Timor Tengah Utara (Studi Kasus Kecamatan Biboki Anleu) - Boanerges Putra Sipayung; Simon Juan Kune; Agustinus Nubatonis; Yohanes Pebrian Vianney Mambur (AGRIMOR, 2021)
Subsidized fertilizer is one of the policies carried out by the government to increase agricultural production, especially food crops. This study aims to analyze the decision making of farmers to buy and use subsidized fertilizers, as well as the preferences of farmers in Biboki Anleu Subdistrict to use subsidized fertilizers. The research was carried out in June-August 2021. Quantitative description methods and logistic regression were used to analyze this study. The number of samples used in this study amounted to 320 respondents. The results of this study are the area of ​​land, the performance of the extension worker, knowledge, the amount of production affect the decision of farmers to buy subsidized fertilizer. Decision making by farmers is significantly influenced by land area, performance of extension workers, knowledge, and ability to access information. The opinion and performance of the extension worker, land area, ability to access information and purchase fertilizer at official kiosks are the preferences of lowland rice farmers.